Tax policies for inclusive growth : prescription versus practice - Hagemann, Robert P. (Paris, 2018)
"Against a backdrop of the widening income distribution in most countries, OECD governments need to formulate policies that support sustainable and inclusive economic growth. Tax policies play a crucial role in this endeavour. Both tax theory and mounting empirical evidence suggest that many countries could achieve both higher and more broadly shared income growth. Many countries, however, seem hesitant to fundamentally restructure their tax systems to achieve higher and more inclusive growth. This reluctance begs a key question: Why forego tax policy reforms that hold the obvious promise of win-win outcomes of both higher and more inclusive growth? To offer some concrete answers to this question, this paper reports the findings of a synthesis of cross-country empirical work on the ranking (in terms of efficiency and distributional impact) of major tax instruments on the one hand, and, on the other, country-specific tax policy assessments reported in several dozen OECD Economic Surveys since 2008. The paper identifies a wide range of factors, some common to many countries and some country-specific, that prevent governments from adopting tax structures more favourable to inclusive growth. These include political economy forces, legal obstacles, administrative constraints, and intergovernmental fiscal arrangements."